Coagulation and inflammation in scrub typhus and murine typhus--a prospective comparative study from Laos. - Paris, D; Chansamouth, V; Nawtaisong, P; Löwenberg, E; Phetsouvanh, R; Blacksell, S; Lee, S; Dondorp, A; van der Poll, T; Newton, P; Levi, M; Day, N (2012)
Scrub typhus (caused by Orientia tsutsugamushi) and murine typhus (caused by Rickettsia typhi) cause up to 28% of febrile episodes in Thailand and Laos. The current understanding of coagulation and inflammation in the pathogenesis of these clinically very similar vasculotropic diseases is limited. This study compared human in vivo changes in 15 coagulation, inflammation and endothelial activation markers in prospectively collected admission and follow-up samples of 121 patients (55 scrub typhus, 55 murine typhus, and 11 typhus-like illness) and 51 healthy controls from Laos. As compared with controls, all but one of the markers assessed were significantly affected in typhus patients; however, the activation patterns differed significantly between scrub and murine typhus patients. The levels of markers of coagulation activation and all inflammatory cytokines, except for interleukin-12, were significantly higher in patients with scrub typhus than in those with murine typhus. In patients with murine typhus, however, the levels of endothelium-derived markers were significantly higher. Anticoagulant factors were inhibited in both typhus patient groups. This is the first study demonstrating that, in scrub typhus, in vivo coagulation activation is prominent and is related to a strong proinflammatory response, whereas in murine typhus, changes in coagulant and fibrinolytic pathways are suggestive of endothelial cell perturbation. These data suggest that, although late-stage endothelial infection is common in both diseases, the in vivo pathogenic mechanisms of R. typhi and O. tsutsugamushi could differ in the early phase of infection and may contribute to disease differentiation.